Utilization Of The Puppet Stage As A Method Of Contextual Evangelism To Sunday School Children Aged 5-10 Years - Agnes Alicia; Ayu Rotama Silitonga; Agustina Bela; Ayang Emiyati (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
Children's ministry is very motivating for the church and child servants because it affects the growth of the child's faith. One of them is the ministry of evangelism. Evangelism is the message of salvation and judgment in Christ Jesus. Children aged 5 - 10 years do not usually understand and interpret themselves as